X-ray photoelectron spectroscopy, x-ray absorption spectroscopy, and x-ray diffraction characterization of CuO-TiO2-CeO2 catalyst system - Francisco, MSP; Nascente, PAP; Mastelaro, V. R.; Florentino, A. O. (American Institute of Physics (AIP), 2001)
X-ray photoelectron spectroscopy (XPS), x-ray diffraction (XRD), and x-ray absorption spectroscopy (XAS) techniques have been applied to characterize the surface composition and structure of a series of CuO-TiO2-CeO2 catalysts. For a small loading of cerium, ceria was mainly dispersed on the titania surface and a minor amount of CeO2 crystallite appeared. At higher loading of cerium, the CeO2 phase increased and the atomic Ce/Ti ratio values were smaller than the nominal composition, as a consequence of cerium agglomeration. This result suggests that only a fraction of cerium can be spread on the titania surface. For titanium-based mixed oxide, we observed that cerium is found as Ce3+ uniquely on the surface. The atomic Cu/(Ce+Ti) ratio values showed no influence from cerium concentration on the dispersion of copper, although the copper on the surface was shown to be dependent on the cerium species. For samples with a high amount of cerium, XPS analysis indicated the raise of second titanium species due cerium with spin-orbit components at higher binding energies than those presented by Ti4+ in a tetragonal structure. The structural results obtained by XAS are consistent with those obtained by XRD and XPS. (C) 2001 American Vacuum Society.